Metaphors in Newspaper Reports on Nigeria 2005 Banks Recapitalisation - Oluremi, Tolulope (Linguistik Online, 2021)
This article investigates metaphors in newspaper reports that border on mergers and acquisitions within the 2005 recapitalisation exercise in Nigeria. It considers conceptual metaphors used in depicting mergers and acquisitions among Nigerian banks and how they are deployed by journalists in shaping readers’ perception of the mergers and acquisitions activities. Data for the study comprise thirty purposively sampled articles on recapitalisation published between year 2004 and 2006, in three selected Nigerian newspapers: Business Day, The Punch and ThisDay, which had relevance, wide circulation and adequate reports on economic issues in Nigeria. Lakoff and Johnson’s (1980) conceptual metaphor theory provides the theoretical perspective for the data analysis. The study reveals two conceptual metaphors: MERGERS AND ACQUISITIONS AS WAR and MERGERS AND ACQUISITIONS AS CONNUBIAL RELATIONS. The metaphors of war influence readers’ perception of the mergers and acquisitions exercise as a corporate management task that is highly indispensable, confrontational and susceptible to aggression considering the appalling state of the Nigeria banking sector and the huge recapitalisation funds required of individual banks. While the connubial metaphors offered readers a perception of an important exercise that entails due process, cooperation, and togetherness in achieving the stipulated recapitalisation funds. Metaphors perform multifarious functions in the construction and comprehension of financial issues. They are not the consequence of genus, but the sequence of motivated cognitive devices used by Nigerian journalists in rendering contemporary Nigerian issues.